On the question of the method of using didactic tools for organizing students' independent work on descriptive geometry - Melkozerovа, Людмила (Рroblems of engineering and professional education, 2023)
The article is devoted to the use of didactic structures in the current work of a student organized by a master of graphic geometry in a higher educational institution. The author has prepared a variety of e-learning tools (daris, practikalyq, SOÖJ, SÖJ) okylady.